Palaeoecological significance of the "wolf event" as revealed by skull ecometrics of the canid guilds. (1st April 2022) - Meloro, Carlo; Sansalone, Gabriele
Abstract: Members of the mammalian order Carnivora are rarely considered as proxies for palaeoecological reconstructions due to their broad phenotypic plasticity and high climatic tolerance. However, palaeontologists have traditionally interpreted the appearance of some particular carnivoran species in relation to major climatic events. The 'wolf event' characterised the inset of climatic deterioration for continental Eurasian fauna, ca 2.0 million years ago. It was defined as the dispersal of cursorial wild canids from East Asia to Europe consequently to the spread of the steppe environment. Anecdotal interpretations were never supported by rigorous testing about the palaeoecological significance of these canid taxa. Here, we employ two dimensional geometric morphometrics of canid skulls to characterise and interpret the structure of extant guilds and its relationship with climate and provide inferences on the early Pleistocene Valdarno community. Averaged skull size and shape of canid guilds are currently associated with climatic parameters that reflect annual mean temperature, seasonality and precipitation. The canid guild from Valdarno showed a clustered phylogenetic structure and its average shape resembles those of communities characterised by relatively high seasonal environments. This study supports the use of canid community structure for palaeoclimatic reconstructions and validate the early Pleistocene as a period of climatic deterioration for Eurasian large mammal fauna. Highlights: Living canids show considerable morphological variation in the skull. Skull shape changes between canid communities are linked to climate and evolutionary history. The fossil canid community of Valdarno (ca 2.0 Ma) was adapted to highly seasonal environments. Canid skull shape can be successfully employed in the palaeoclimatic reconstruction of Quaternary fossil sites.